Business Plan : Teruna Bakery Enterprise / Muhammad Azamuddin Zulkornan … [et al.] - Zulkornan, Muhammad Azamuddin; Jusoh, Muhammad Aiman; Ahmad, Muhammad Syahir; Kamaruzaman, Muhammad Rusydan; Zulkifli, Muhammad Zul Hafiy (2021)
Teruna Bakery Enterprise, the business product-based oriented that are targeting satisfaction through dessert and sweets with affordable price because it used a high-quality ingredients and equipment throughout the product making. The owner of the Teruna Bakery Enterprise consist of a 5 people which are entrepreneur named Muhammad Rusydan Kamaruzaman as General Manager, Muhammad Aiman Jusoh as Operational Manager, Muhammad Azamuddin Zulkornain as Marketing Manager, Muhammad Zul Hafiy Zulkifli as Administration Manager and Muhammad Syahir Ahmad as Financial Manager, line of entrepreneurs from Kelantan with their main 4 product which are Chocolate Larva Indulgence Cake, Fluffy Cloud Pavlova Cake, Teruna Red Velvet Cake and Flooded Mango Creamy Cake. Our target customers consist literally everyone especially the dessert food lover, food hunter squad and pastry chef out there. We target those people because they tend to satisfy themselves with food and even buy plenty of dessert either for own self or other people. Not all customers will tend to satisfy their buying decision when it comes to post-purchase behavior. With that, our business provides sample tester cake to make them feel our loved by caked and can decide which food they will buy and fulfilling their desire and expectation. The Teruna Bakery Enterprise are located in Kubang Kerian, Kota Bharu, Kelantan but it is enlarging towards other district and state because the demand increased as our target customer become bigger and interested in our product. The operation of The Teruna Bakery Enterprise is in higher equipment because the upgrades from the traditional towards the modern process, but the taste will the same to make the quality still the same. The financial of Teruna Bakery Enterprise became higher and receive more profit because of the attractive towards our products from the customers. Referring to the marketing plan, our service strategy is by hiring specialize staff that can do all the altering services efficiently to satisfy the customer. We also offer affordable prices to the customer and it depends to the type of altering services that they need. Demand during that time will increase and our sales will increase as well. We also serve the best quality of services to reduce defect item. It will reduce the cost from the wastage and increase our profit. We will expect that Teruna Bakery Enterprise will become more developed soon because if the more quality services provided in Kota Bharu, the demand will increase not only during any occasion, but it might be a new daily dessert. This will give more advantage to our shop to increase sales and be profitable.